Trade of Nepal During the Mid-20th Century - Ghimire, Gopal Prasad (Tejganga Darpan, 2024)
The international trade has existed in Nepal since the 8th century. Nepal advanced significantly from ancient to medieval periods. Current time, Nepal faces the trade deficit with the foreign country. This study focuses to inform the condition of trade of Nepal during the 20th century. That is the trade pattern of Nepal during the Rana dynasty. The objective of the study is to explore the international trend of Nepal during the mid- 20th century. This study employs secondary data of the trade of Nepal in mid-20th century to British-India. Up to the early 20th century, Nepal experienced a trade surplus, primarily exporting raw materials and importing finished goods from British-India. This research employs a historical approach. This research paper informs the scenario of trade of Rand dynasty of Nepal to the entire academic’s ordinary people.